Four new species of hangingflies (Insecta, Mecoptera, Bittacidae) from the Middle Jurassic of northeastern China - Liu, Sulin (Zookeys, 2014)
Abstract. Two new species of Mongolbittacus Petrulevičius, Huang & Ren, 2007, Mongolbittacus speciosus sp. n. and Mongolbittacus oligophlebius sp. n., and two new species of Exilibittacus Yang, Ren & Shih, 2012, Exilibittacus foliaceus sp. n. and Exilibittacus plagioneurus sp. n., in the family Bittacidae, are described and illustrated based on five well-preserved fossil specimens. These specimens were collected from the late Middle Jurassic Jiulongshan Formation of Daohugou, Inner Mongolia, China. These new findings enhance our understanding of the morphological characters of early hangingflies and highlight the diversity of bittacids in the Mid Mesozoic ecosystems.